Digital Difference: Theorizing Frameworks of Bodies, Representation and Stereotypes in Digital Games. (June 2016) - Cover, Rob
This article presents a theoretical framework for making sense of gaming, ethnicity and race through the conceptual lens of critical approaches to the body, representation and the relationship between bodies and technologies of gameplay. Taking the view that gaming is a core activity of contemporary digital sociality that always involves bodies, whether represented on-screen or as game-players who are neither disembodied nor radically separated from those on-screen re-presentations, this article addresses the fact that, in everyday social life, stereotypes of representations of bodies of difference circulate in embedded ways in all communicative activities including digital gaming. However, if re-thinking the relationship of the body and its on-screen representations through assemblages of bodies–technologies beyond the more rudimentary real/virtual distinctions of older conceptualizations of media use, it is possible to open new critical frameworks for addressing race and ethnicity discrimination in the contemporary activity and performativity of gameplay. This article begins with a brief introduction to critical approaches to the body, followed by a discussion of on-screen representation and bodily stereotyping, finishing with an analysis of the relationship between bodies, gaming avatars and mutually constitutive body–technology relationships.